Identity Contestation in the Linguistic Landscape of Pantai Indah Kapuk 2, Jakarta (Kontestasi Identitas dalam Lanskap Linguistik Kawasan Pantai Indah Kapuk 2, Jakarta) - Anis Rahmawati; Novi Anoegrajekti; Samsi Setiadi (Jurnal Gramatika, 2023)
Pantai Indah Kapuk 2 area is a new area developed by the Salim Group and Agung SedayuGroup. The area consists of housing, tourist areas, and commercial areas. Pantai Indah Kapuk 2 area is arepresentation of a modern community area in the city of Jakarta. In the area, educational facilities, jobs, various types of new businesses, and so on are developing. These conditions affect the linguistic landscape of Pantai Indah Kapuk 2, which trends towards multilingual conditions. A striking trend is theuse of foreign language structures and word choices, especially English and Chinese, on public spacesigns. This trend appears in the naming of housing, public facilities, billboards, etc., which seems to showthat the community is "very literate in globalization and modernization". This research will examine thelinguistic landscape using semiotic and language policy approaches. The multilingual condition in thePantai Indah Kapuk area shows the tension of national language policy on language use. This study will reveal the linguistic landscape pattern that illustrates that language choice is not done carelessly.